Free‐running 5D coronary MR angiography at 1.5T using LIBRE water excitation pulses. Issue 3 (6th March 2020) - Masala, Nemanja; Bastiaansen, Jessica A. M.; Di Sopra, Lorenzo; Roy, Christopher W.; Piccini, Davide; Yerly, Jérôme; Colotti, Roberto; Stuber, Matthias
Abstract : Purpose: To implement, optimize, and characterize lipid‐insensitive binomial off‐resonant RF excitation (LIBRE) pulses for fat‐suppressed fully self‐gated free‐running 5D cardiac MRI. Methods: Bloch equation simulations were used to optimize LIBRE parameter settings in non‐interrupted bSSFP prior to in vitro validation. Thus, optimized LIBRE pulses were subsequently applied to free‐running coronary MRA in 20 human adult subjects, where resulting images were quantitatively compared to those obtained with non‐fat‐suppressing excitation (SP), conventional 1‐2‐1 water excitation (WE), and a previously published interrupted free‐running (IFR) sequence. SAR and scan times were recorded. Respiratory‐and‐cardiac‐motion‐resolved images were reconstructed with XD‐GRASP, and contrast ratios, coronary artery detection rate, vessel length, and vessel sharpness were computed. Results: The numerically optimized LIBRE parameters were successfully validated in vitro. In vivo, LIBRE had the lowest SAR and a scan time that was similar to that of WE yet 18% shorter than that of IFR. LIBRE improved blood–fat contrast when compared to SP, WE, and IFR, vessel detection relative to SP and IFR, and vessel sharpness when compared to WE and IFR (for example, for the left main and anterior descending coronary artery, 51.5% ± 10.2% [LIBRE] versus 42.1% ± 6.8% [IFR]). Vessel length measurements remained unchanged for all investigated methods. Conclusion: LIBRE enabled fully self‐gated non‐interrupted free‐running 5D bSSFP imaging of the heart at 1.5T with suppressed fat signal. Measures of image quality, vessel conspicuity, and scan time compared favorably to those obtained with the more conventional non‐interrupted WE and the previously published IFR, while SAR reduction offers added flexibility.